77.0k views
4 votes
Select the correct answer.
What is the factored form of this expression?
x2 - 7x + 12

User Sulabh
by
5.7k points

2 Answers

1 vote

Answer:

(x-4)(x-3)

Explanation:

x²- 7x+12

=x²-4x-3x+12 applying midterm break

=x(x-4) -3(x-4)

=(x-4)(x-3)

User Onur Eker
by
6.1k points
5 votes

Answer:

x = 3, x= 4 are the factors of the equation.

Explanation:

x² - 7 x + 12 = 0

x² -4 x - 3 x + 12 = 0

x ( x - 4) - 3 ( x - 4 ) = 0

(x - 3) ( x - 4) = 0

x = 3, x = 4

Hence x = 3, x= 4 are the factors of the equation.

User Pmagunia
by
6.0k points